POLA MAKAN SEBELUM, SELAMA DAN SETELAH LATIHAN SERTA KEBUGARAN FISIK ATLET SEPAK TAKRAW - Ni_Kadek Wulandari; Ni Made Dewantari; I Wayan Ambartana (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
In general fitness is a series of one's ability to do specific physical activities. Eating patterns before, during and after exercise requires food both in terms of quantity, quality, variety and strategy. The purpose of this study was to determine eating patterns before, during and after exercise and physical fitness of takraw athletes at the Takraw Football Association of Bangli Regency. This type of research is observational with a cross sectional study design and 24 samples were taken. The data taken include eating patterns collected form recall, physical fitness by measuring VO2 max using a multi-stage run test (bleep test). The data obtained is processed according to the type of data and research objectives. Data analysis using frequency distribution tables and cross tables and then described descriptively. The linkage of physical fitness based on the type of food before exercise are mostly in the inappropriate category (83,33%), the linkage of physical fitness based on protein consumption are mostly below average (83,33%) and the linkage of physical fitness based on the meal times before exercises are mostly in the inappropriate categories (77,78%). The linkage of physical fitness based on the type of food after exercise are mostly in the appropriate category (88,89%), the linkage of physical fitness based on fat consumption are mostly below average (83,33%) and the linkage of physical fitness based on mealtime after exercise are mostly in the appropriate category (88,89%). Conclusion there is a tendency of distribution of physical fitness based on the type of meal before exercise and meal time before exercise.Keywords: physical fitness, diet, sepak takraw